Motivation for raw milk consumption among Malaysians / Mohd Ikhmal Hanif Abdul Khalid and Nuraini Mahror - Abdul Khalid, Mohd Ikhmal Hanif; Mahror, Nuraini (Universiti Teknologi MARA Cawangan Pahang, 2020)
Raw or unpasteurized milk is rich with beneficial nutrients including calcium, potassium, phosphorus and vitamins. Recently, there was a tremendous demand for raw milk in the local market. However, consumption of raw milk is risky as its commonly associated with food born disease outbreaks. Therefore, this study aimed to identify the motivations for unpasteurized milk consumption among Malaysians. A total of 180 respondents had participated in this survey and a questionnaire was distributed via social media. The result revealed that majority of the consumers were female, Malay, aged between 21 to 30 years old, a bachelor degree holder and were living in an urban area. The motivation for raw milk consumption was dominated by the belief that raw milk possesses holistic health benefits followed by taste, prevention of immune-related disease, support for local farm and the belief that processed milk is not safe. The consumers had moderate knowledge about the health benefits and health risks associated with raw milk (M=3.30, SD=1.048). However, most respondents were not aware that selling raw milk is illegal in Malaysia. There was no significant difference between male and female consumers’ perception regarding health benefits and health risk associated with raw milk (t=1.637, df= 69.037, p-value 0.11) at 95% confident interval.